I have been stuck in this proof for a while. This should not be a long shot.

Claim If $x_n>0$ for all $n\in N$, then $1+nx_n\leq (1+x_n)^n$.

My strategy is to use Induction Theorem and Binomial Theorem, which does not work quite well.

My proof If $n=1$, $1+x_1\leq (1+x_1)^1$ (True).

Assume this claim is true for $n$. Consider $n+1$:

$(1+x_{n+1})^{n+1}=x_{n+1}^{n+1}+(n+1)x_{n+1}^n+\dots+2x_{n+1}+1$. (**)

Need to show $(**)\geq 1+(n+1)x_{n+1}$, given $(1+nx_n)\leq (1+x_n)^n$, i.e. $(1+nx_n)\leq x_n^n+nx_n^{n-1}+\dots + 2x_n+1$.

Could someone give me a hint on how to deal with the $n+1$ case? In particular, how to link $x_n$ to $x_{n+1}$, if induction is the right way to go? Thanks in advance!

  • 4
    $\begingroup$ $(1+x)^{n+1}=x^{n+1}+\cdots+(n+1)x+1$. $\endgroup$ – Lord Shark the Unknown Aug 1 '18 at 3:19
  • 1
    $\begingroup$ Try multiplying both sides of $(1+x)^n\ge1+nx$ by $1+x$. $\endgroup$ – Simply Beautiful Art Aug 1 '18 at 3:20
  • 1
    $\begingroup$ Just prove that $\forall x>0\;\forall n\in \Bbb N\;(1+nx\leq (1+x)^n))$ by induction on $n$. $\endgroup$ – DanielWainfleet Aug 1 '18 at 4:18

The way I look at this one is to temporarily forget about the index $n$ on the $x_n$ and simply note that, for any real $y > 0$ and $1 \le n \in \Bbb N$,

$1 + y \le 1 + ny \le \sum_0^n \dfrac{n!}{i!(n - i)!} 1^{n - i} y^i = (1 + y)^n, \tag 1$

which follows from the binomial theorem applied to $(1 + y)^n$; since (1) holds for every $n$, we may successively set $y = x_n$ for any positive real sequence $x_n$ and obtain

$1 + x_n \le (1 + x_n)^n \tag 2$

for each $n$.

The fact is that the problem specifies no relationship 'twixt $x_n$ and $x_{n + 1}$, etc., so attempting to use one as a means of solution is ill-founded; the $x_n$ are arbitrary and independent.

So it's really all about (1). The essential relaitionship

$1 + y \le (1 + y)^n \tag 3$

can in fact be proved by induction without resorting to the binomial theorem: if

$1 + y \le (1 + y)^k, \tag 4$

then since

$1 < 1 + y, \tag 5$

we have

$1 + y < (1 + y)(1 + y) \le (1 + y)^k (1 + y) = (1 + y)^{k + 1}. \tag 6$

"About binomial theorem I am teeming with a lot of news,

With many cheerful facts about the square of the hypoteneuse!"

--Gilbert & Sullivan, "Modern Major General".


Note that the induction doesn't work here because you have not a relation between $x_n$ and $x_{n+1}$. You need to prove the inequality for every fixed $n$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.